PERJANJIAN KARTEL SEBAGAI BENTUK PERSAINGAN USAHA TIDAK SEHAT DALAM KASUS PT. YAMAHA DAN PT. ASTRA HONDA - Bagus Alief Massayyid; Aldira Mara Ditta Caesar Purwanto; Teddy Prima Anggriawan (Universitas Katolik Widya Karya Malang, 2023)
Trade is a very promising livelihood. Where in addition to the community, there are also relatively many supporters of the trade process, trade itself is a livelihood that can promise high levels of prosperity by business actors. It's just that the problem in a competition is what is called fair competition or unhealthy competition. Here it is clear that the problem is unhealthy competition where there is a lot of competition. deviation where the deviation causes one of the parties to be harmed. One example of a case of unfair business competition is the Cartel Agreement as a Form of Unfair Business Competition in the Case of PT. Yamaha Indonesia Motor Manufacturing and PT. Astra Honda Motor. Unfair business competition can result in a party losing money and can damage the smooth progress of the local and world economy. Therefore, before it's too late to overcome unfair business competition, we must prevent that from happening. If it is proven that the business actor committed fraud in business competition, namely carrying out prohibited activities which resulted in monopolistic practices and or unfair business competition, then the sanction that will be obtained can be in the form of administrative action.